2013
DOI: 10.1097/meg.0b013e32835c2af3
|View full text |Cite
|
Sign up to set email alerts
|

Blood neutrophil-to-lymphocyte ratio independently predicts survival in patients with liver cirrhosis

Abstract: NLR is a predictor of mortality independent of CTP and MELD scores in patients with liver cirrhosis. NLR could predict mortality in the subgroup of patients with low MELD scores as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
113
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 25 publications
4
113
0
2
Order By: Relevance
“…More importantly, the NLR could predict mortality in patients with low MELD and/or CTP scores. 41 Furthermore, neutrophil gelatinase-associated lipocalin was found to be a predictor of mortality in cirrhosis patients with hepatorenal syndrome. 42 Anti-neutrophil cytoplasmic antibodies are a non-uniform family of antibodies that recognizes diverse neutrophil components.…”
Section: Neutrophils and Liver Fibrosis/cirrhosismentioning
confidence: 99%
“…More importantly, the NLR could predict mortality in patients with low MELD and/or CTP scores. 41 Furthermore, neutrophil gelatinase-associated lipocalin was found to be a predictor of mortality in cirrhosis patients with hepatorenal syndrome. 42 Anti-neutrophil cytoplasmic antibodies are a non-uniform family of antibodies that recognizes diverse neutrophil components.…”
Section: Neutrophils and Liver Fibrosis/cirrhosismentioning
confidence: 99%
“…In the literature, the NLR has also been found to be associated with various liver diseases (14,15). In the results of this study, it was observed that the NLR was higher in NASH patients than in the healthy controls and simple liver steatosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophillymphocyte ratio (NLR) is a marker that can be estimated by using leukocyte subtypes from the complete blood count. Moreover, it has been reported that NLR may have prognostic value in some diseases [7,8].In the current literature, there is no study evaluating MPV and NLR together in gout. In this retrospective study, we investigated the role of MPV and NLR in the determining disease activity in gout disease.…”
mentioning
confidence: 99%
“…MPV is indirectly linked to platelet activity. Larger platelets are more active than smaller ones in terms of metabolic and enzymatic activity [4][5][6][7][8][9]. Neutrophillymphocyte ratio (NLR) is a marker that can be estimated by using leukocyte subtypes from the complete blood count.…”
mentioning
confidence: 99%